(untitled) (Jurnal Bina Praja, 2025)
Background of Study: The circulation of narcotics in Indonesia has evolved into a complex, asymmetrical threat, demanding a policy reorientation from a purely punitive approach (war on drugs) to collaborative governance, especially following the enactment of Law No. 1 of 2023 (the National Criminal Code). The problem: A repressive penal approach has proven unsuccessful in reducing prevalence and has instead led to extreme overcapacity in correctional institutions, while regional autonomy has not been optimal in supporting prevention due to sectoral egos. Gap of Study: There has been no comprehensive study that integrates the analysis of the new criminal law transition with the collaborative governance model of local government. Theory: This study uses Friedman’s Legal System Theory (Grand), Barda Nawawi Arief’s Criminal Policy (Middle-Range), and Ansell & Gash’s Collaborative Governance (Applied). Aim: Analyzing the harmonization of penal-non-penal policies and reconstructing a collaborative governance model. Research Question: How is the harmonization of legal construction after Law No. 1 of 2023 and how does the collaborative model overcome institutional fragmentation? Method: Juridical-normative with a sociological approach based on secondary data. Results: The National Criminal Code changes the death penalty into a special penalty with a probationary period, requiring the readiness of a rehabilitation structure. Discussion: The failure of penal is due to the disorientation of the legal structure, while non-penal is hampered by weak regional institutional design. Conclusion: Effective drug control requires a balance between criminal policy and facilitative regional leadership. Recommendation: Implementation of the Hexa-Helix collaboration model and integration of P4GN indicators into regional development planning documents (RPJMD/IKU) and the issuance of rehabilitative prosecution guidelines.